coil

JP7608131B2Active Publication Date: 2025-01-06NITERRA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020197893
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-30
Publication Date
2025-01-06
Estimated Expiration
2040-11-30

AI Technical Summary

Benefits of technology

【0007】 第1の態様によれば、導体を覆う絶縁体はセラミック粒子および非晶質酸化物からなり、セラミック粒子の平均粒径は0.4μm以上10μm以下であり、絶縁体の平均の厚さは1μm以上50μm以下である。絶縁体の切断面において、絶縁体の面積に対するセラミック粒子の面積は50%以上70%以下である。これにより導体と絶縁体との付着性を確保し、さらに絶縁体の熱伝導性を向上できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608131000002
    Figure 0007608131000002
  • Figure 0007608131000003
    Figure 0007608131000003
  • Figure 0007608131000004
    Figure 0007608131000004
Patent Text Reader

Abstract

To provide a coil that can improve the thermal conductivity of an insulator.SOLUTION: A coil is a wound wire provided with a conductor and an insulator covering the conductor, and the insulator consists of ceramic particles and an amorphous oxide. The average thickness of the insulator is 1 μm or more and 50 μm or less, and the average particle size of the ceramic particles is 0.4 μm or more and 10 μm or less. On the cut surface of the insulator, the area of the ceramic particles with respect to the area of the insulator is 50% or more and 70% or less.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coil wound with a wire having a conductor and an insulation covering the conductor. [Background technology]

[0002] As a technique for obtaining wire suitable for coils, Patent Document 1 discloses a technique in which a paint containing polyimide resin or polyamideimide resin and a siloxane-based compound is applied to a conductor, and then an insulator is provided on the conductor by baking. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-132393 A Summary of the Invention [Problem to be solved by the invention]

[0004] In a coil, when the temperature of a conductor rises and the electrical resistance of the conductor increases, the power loss (copper loss) consumed by the resistance component increases.To reduce copper loss, there is a demand to improve the thermal conductivity of the insulator that covers the conductor in order to promote heat dissipation from the conductor and suppress the increase in the conductor's resistance.

[0005] The present invention has been made to meet this demand, and an object of the present invention is to provide a coil capable of improving the thermal conductivity of the insulator. [Means for solving the problem]

[0006] To achieve this object, the coil of the present invention is a wound wire having a conductor and an insulator covering the conductor, the insulator being made of ceramic particles and amorphous oxide. The average thickness of the insulator is 1 μm or more and 50 μm or less, and the average particle size of the ceramic particles is 0.4 μm or more and 10 μm or less. In a cut surface of the insulator, the area of ​​the ceramic particles is 50% or more and 70% or less of the area of ​​the insulator. Effect of the Invention

[0007] According to the first aspect, the insulator covering the conductor is made of ceramic particles and amorphous oxide, the ceramic particles have an average particle size of 0.4 μm to 10 μm, and the insulator has an average thickness of 1 μm to 50 μm. In the cut surface of the insulator, the area of ​​the ceramic particles is 50% to 70% of the area of ​​the insulator. This ensures adhesion between the conductor and the insulator, and further improves the thermal conductivity of the insulator.

[0008] According to the second aspect, the value obtained by dividing the average maximum thickness of the insulator on a cross section cut along a plane perpendicular to the coil axis by the average minimum thickness is equal to or less than 2.4. This reduces the tensile stress generated in the insulator due to thickness variation, and in addition to the effect of the first aspect, improves the adhesion between the conductor and the insulator.

[0009] According to the third aspect, the material of the ceramic particles is at least one selected from aluminum nitride, silicon carbide, and silicon nitride, which can further improve the thermal conductivity in addition to the effects of the first and second aspects.

[0010] According to the fourth aspect, the main component of the amorphous oxide is Bi or Te, which can improve the adhesion of the insulator in addition to the effects of any one of the first to third aspects.

[0011] According to the fifth aspect, the material of the conductor is Cu or Al. In addition to the effects of any one of the first to fourth aspects, the thermal conductivity and electrical conductivity of the conductor can be ensured. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a perspective view of a coil according to an embodiment. [Diagram 2] FIG. [Diagram 3] 1 is a cross-sectional view of a wire cut along a plane perpendicular to the axis of the coil. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, preferred embodiments of the present invention will be described with reference to the accompanying drawings. FIG. 1 is a perspective view of a coil 10 in one embodiment. The coil 10 is a wire 11 wound in a spiral shape around an axis C. The coil 10 in this embodiment is a winding in which the wire 11 is edgewise bent. The coil 10 is a square tube, and the outer shape of the coil 10 is a rectangle with adjacent sides connected by arcs when viewed in the axial direction of the coil 10 from the axis C. Examples of applications of the coil 10 include motors, generators (rotating electric machines), reactors, and transformers, but there is no limitation to the applications. The coil 10 may be an air-core coil without a magnetic core.

[0014] Fig. 2 is a cross-sectional view of wire 11 including axis C (see Fig. 1) of coil 10. Wire 11 is an insulated wire including conductor 12 and insulator 13 covering conductor 12. Examples of the material of conductor 12 include Cu, Al, and alloys of Cu and Al. Conductor 12 in this embodiment is a rectangular wire (single wire) with rounded corners. Conductor 12 may be an assembled wire formed by gathering multiple single wires. An example of an assembled wire is one in which multiple single wires are stacked.

[0015] 3 is a cross-sectional view of the wire 11 cut along a plane P (see FIG. 1) perpendicular to the axis C of the coil 10. The insulator 13 is made of ceramic particles 14 and an amorphous oxide 15. The amorphous oxide 15 (glass) is attached to the conductor 12. In the insulator 13, the gaps created by the ceramic particles 14 are filled with the amorphous oxide 15. The ceramic particles 14 fixed to the amorphous oxide 15 improve the thermal conductivity, toughness, and strength of the amorphous oxide 15.

[0016] In order to reduce thermal deterioration of the insulator 13, the insulator 13 does not contain resin. The thermal conductivity of a resin material is generally 0.25-0.30 W / mK, and the thermal conductivity of the amorphous oxide 15 is 0.60 W / mK or more. The thermal conductivity of the amorphous oxide 15 is generally higher than that of a resin, and therefore the thermal conductivity of the insulator 13 can be improved. The fact that the insulator 13 does not contain resin can be determined by the appearance of the material appearing on the cross section of the insulator 13, and by wavelength dispersive X-ray analysis (WDS) of the material using an electron probe microanalyzer (EPMA) showing that the carbon contained in the material is below the detection limit.

[0017] Examples of the material of the ceramic particles 14 include oxides such as alumina, zirconia, mullite, and titania; nitrides such as aluminum nitride, silicon nitride, zirconium nitride, and titanium nitride; carbides such as silicon carbide and titanium carbide; and borides such as titanium boride. Ceramic particles 14 made of at least one material selected from aluminum nitride, silicon oxide, and silicon nitride are particularly suitable for improving the thermal conductivity of the insulator 13. Ceramic particles 14 may be made of a mixture of different materials.

[0018] The average particle size of the ceramic particles 14 is preferably 0.4 μm or more and 10 μm or less in order to ensure the strength of the insulator 13. The average particle size of the ceramic particles 14 is obtained as follows. First, an image of a cross section of the insulator 13 in which 50 or more ceramic particles 14 appear is obtained. Next, the circle-equivalent diameter (diameter) of the area of ​​each of the 50 or more ceramic particles 14 is obtained by image analysis. The average particle size of the ceramic particles 14 is the average value (n≧50) of the obtained circle-equivalent diameters.

[0019] The amorphous oxide 15 may be, for example, a material containing one selected from the group consisting of Si, B, P, Te, and Bi as a main component. The main component of the amorphous oxide 15 refers to an element (having the largest amount of substance) contained in the amorphous oxide 15 among elements other than oxygen (O). In addition to O and the main component element, the amorphous oxide 15 may contain one or more elements selected from alkali metals such as Li, Na, and K; alkaline earth metals such as Mg, Ca, and Ba; poor metals such as Al; and transition metals such as Ti and Zn.

[0020] The insulator 13 may contain impurities other than the ceramic particles 14 and the amorphous oxide 15. Examples of the impurities include oxides of metal elements or nonmetal elements and C. The oxides (impurities) are present, for example, at the interface 16 between the conductor 12 and the insulator 13. C (impurity) is present, for example, at the boundary between the ceramic particles 14 and the amorphous oxide 15 or in the amorphous oxide 15.

[0021] Examples of metal elements constituting the oxides (impurities) include transition metals such as Cr and Cu; semimetals such as Si; and poor metals such as Al. An example of a nonmetal element constituting the oxides (impurities) is C. The content of the impurities is 1 wt % or less in terms of oxide with respect to the insulator 13. Analysis of the impurities can be performed by WDS using an EPMA, inductively coupled plasma (ICP) optical emission spectroscopy, or energy dispersive X-ray analysis (EDS) using a transmission electron microscope (TEM).

[0022] The insulator 13 is provided around the entire circumference of the conductor 12 in the cross section of the wire 11 including the axis C of the coil 10. This is to ensure insulation at least between adjacent conductors 12. The insulator 13 has an average thickness of 1 μm or more and 50 μm or less. This is to ensure adhesion between the conductor 12 and the insulator 13. An oxide film formed on the surface of the conductor 12 may be present at the interface 16 between the conductor 12 and the insulator 13.

[0023] The thickness of the insulator 13 is the distance between the interface 16 and the surface of the insulator 13 in the normal direction of the interface 16. The thickness of the insulator 13 is determined by image analysis of the cross section of the wire 11 cut on a plane P (see FIG. 1) perpendicular to the axis C of the coil 10. The image can be obtained after dividing the coil 10 into pieces of a size suitable for cross-sectional observation. The average thickness of the insulator 13 is the average distance between the interface 16 and the surface of the insulator 13 in the range where the length of the interface 16 appearing in the cross section of the insulator 13 is 3 mm or more. If an oxide film is present at the interface 16, the thickness of the insulator 13 should not include the thickness of the oxide film.

[0024] On the cut surface of the insulator 13, the area of ​​the ceramic particles 14 is 50% or more and 70% or less of the area of ​​the insulator 13. This is to improve the thermal conductivity of the insulator 13. The areas of the insulator 13 and the ceramic particles 14 are obtained by image analysis of the cross section of the wire 11. To improve accuracy, the minimum value of the range (area) of the image for determining these areas is set to 90,000 μm2 on the cut surface of the insulator 13. 2 Images are obtained from three or more locations of the insulator 13, the ratio of the area of ​​the ceramic particles 14 is calculated from each image, and the average value is regarded as the area of ​​the ceramic particles 14 relative to the area of ​​the insulator 13.

[0025] The porosity of the cut surface of the insulator 13 is preferably 7% or less. This is to improve the thermal conductivity of the insulator 13. The porosity of the insulator 13 is calculated as follows. The cut surface of the insulator 13 is observed with a scanning electron microscope (SEM) and an image of the cross section of the insulator 13 is obtained. The porosity is calculated by dividing the area of ​​the voids calculated by image processing by the area of ​​the image (%). To improve accuracy, the minimum range (area) of the image for calculating the void area is set to 90,000 μm2 on the cut surface of the insulator 13. 2 Images are obtained from three or more positions of the insulator 13, the porosity is calculated from each image, and the average value is regarded as the porosity of the insulator 13.

[0026] The coil 10 is manufactured, for example, by the following method. First, a winding in which the conductor 12 is shaped into the shape of the coil 10 and a liquid in which electrically charged ceramic particles 14 are dispersed are prepared. The winding is submerged in the liquid, and a film of the ceramic particles 14 is formed on the surface of the conductor 12 by electrodeposition. The film on the surface of the conductor 12 also contains the resin dispersed in the liquid, so after removing the winding from the liquid and washing it, the winding is heated to burn off the resin contained in the film. Residues of the chemicals used in the pretreatment for electrodeposition and carbonized resin may remain as impurities.

[0027] Next, an amorphous oxide 15 is formed on the surface of the conductor 12, and the ceramic particles 14 are fixed to the conductor 12 by the amorphous oxide 15. Methods for forming the amorphous oxide 15 (glass) on the surface of the conductor 12 include a melting method, a gas phase method, a sol-gel method, and the like. This results in a coil 10 in which the conductor 12 is covered with an insulator 13 consisting of the ceramic particles 14 and the amorphous oxide 15. An insulating varnish may be applied to the coil 10 as necessary.

[0028] In the coil 10, the insulator 13 covering the conductor 12 is made of ceramic particles 14 and amorphous oxide 15. The average thickness of the insulator 13 is 1 μm or more and 50 μm or less. The average particle size of the ceramic particles 14 is 0.4 μm or more and 10 μm or less. On a cut surface of the insulator 13, the area of ​​the ceramic particles 14 relative to the area of ​​the insulator 13 is 50% or more and 70% or less. This ensures adhesion between the conductor 12 and the insulator 13, and further improves the thermal conductivity of the insulator 13.

[0029] Since the insulator 13 does not contain resin, it is possible to reduce thermal deterioration of the insulator 13 caused by resin, and therefore it is possible to reduce deterioration of the thermal conductivity of the insulator 13 over time.

[0030] The value X / N obtained by dividing the average maximum thickness X of the insulator 13 by the average minimum thickness N of the insulator 13 in the cross section of the wire 11 cut along a plane P (see FIG. 1) perpendicular to the axis C of the coil 10 is preferably 2.4 or less. If X / N≦2.4, the tensile stress of the insulator 13 caused by the variation in thickness can be reduced, and the adhesion between the conductor 12 and the insulator 13 can be improved.

[0031] The average maximum thickness X of the insulator 13 is the average value of five maximum values ​​obtained by image analysis from five locations of the insulator 13 appearing in the cross section of the wire 11 cut along the plane P. The average minimum thickness N of the insulator 13 is the average value of five minimum values ​​obtained by image analysis from the same five locations as those from which the average maximum thickness X was obtained. The range (one of the five locations) for obtaining each of the average maximum thickness X and the average minimum thickness N is a range in which the length of the interface 16 appearing in the cross section of the insulator 13 is 300 μm or more. If an oxide film is present at the interface 16 between the conductor 12 and the insulator 13, the thickness of the insulator 13 is set so as not to include the thickness of the oxide film.

[0032] The material of the ceramic particles 14 is preferably at least one selected from aluminum nitride, silicon carbide, and silicon nitride, because this can further improve the thermal conductivity of the insulator 13.

[0033] The main component of the amorphous oxide 15 is preferably Bi or Te, because this can improve the adhesion of the insulator 13.

[0034] The material of the conductor 12 is preferably Cu (electrical copper material) or Al (electrical hard aluminum), because this ensures the thermal conductivity and electrical conductivity of the conductor 12. EXAMPLES

[0035] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0036] Sample No. 1-25 shown in Table 1 was prepared in which all surfaces of a conductor made of a rectangular wire with a thickness of 5 mm and a constant width were covered with insulation. Sample No. 1-25 differed in the conductor material, the ceramic particles and amorphous oxide materials and their ratios contained in the insulator, the porosity of the insulator, and the average thickness of the insulator.

[0037] [Table 1] The insulators of samples No. 1-20 and 23-25 ​​have a porosity (%) equal to the sum of the areas (%) of ceramic particles and amorphous oxides, which is 100%. The insulators of samples No. 21 and 22 do not contain amorphous oxides. The insulator of sample No. 21 contains 31 vol% epoxy resin instead of amorphous oxides. The insulator of sample No. 22 contains 23 vol% epoxy resin instead of amorphous oxides.

[0038] The amorphous oxides of samples No. 1 and 23-25 ​​contain Si (main component), Li, Na, K, Mg, and Ca. The amorphous oxide of sample No. 2 contains B (main component), Na, K, and Mg. The amorphous oxide of sample No. 3 contains P (main component), Li, Na, Ca, and Zn. The amorphous oxide of sample No. 4 contains Si (main component), Li, Na, Mg, Ba, and Zn. The amorphous oxide of samples No. 5-14 contains Si (main component), Li, K, Ba, Zn, and Ti. The amorphous oxide of sample No. 15 contains Te (main component), Zn, Ba, and Al. The amorphous oxide of samples No. 16, 19, and 20 contains Bi (main component), Zn, Ba, and Al. The amorphous oxide of sample No. 17 contains Te (main component), Zn, Mg, Ba, and Al. The amorphous oxide of sample No. 18 contains Te (main component), Zn, Mg, and Al.

[0039] The particle size of the ceramic particles shown in Table 1 is the average value of the circle equivalent diameter of 50 particles appearing on the cross section (rounded to the nearest tenth). The area (%) of the ceramic particles and amorphous oxides, the porosity (%) of the insulator, and the average thickness (μm) of the insulator are the average values ​​of the five cross sections (rounded to the nearest tenth). The maximum thickness (μm) and minimum thickness (μm) of the insulator are the average values ​​of the five cross sections (rounded to the nearest tenth), and indicate the average maximum value X and the average minimum value N, respectively. The thickness ratio (-) is the value obtained by dividing the average maximum value X by the average minimum value N (rounded to the nearest tenth). The adhesion and thermal conductivity properties of the insulator were measured and evaluated for samples No. 1-25.

[0040] (Adhesive) The adhesion test of the insulator was conducted according to the micro scratch test specified in JIS R3255:1997. The test involved pressing an indenter needle against the flat surface of the insulator of the sample, and moving the sample parallel to and linearly along the surface while micro-vibrating the indenter needle horizontally. The complete failure load was measured at which 100% of the insulator in the test area peeled off. The indenter needle was made of diamond, had a cone angle of 120° at the tip, and a radius of curvature of 0.2 mm at the tip. The larger the complete failure load, the stronger the adhesion of the insulator to the conductor. Samples with a complete failure load of 75N or more were rated S, samples with a complete failure load of 60N or more but less than 75N were rated A, samples with a complete failure load of 40N or more but less than 60N were rated B, and samples with a complete failure load of less than 40N were rated C. The results are shown in Table 1.

[0041] (Thermal Conductivity) 5 mm on one side of the sample conductor in the thickness direction 2 A heater with a surface temperature of 80°C was placed on a sample and one side of the sample was heated. The distance between the sample side and the heater surface was 3 mm. The temperature of the other side of the sample in the thickness direction was measured with a radiation thermometer, and a test was conducted to measure the time from when heating of one side of the sample began until the temperature indicated by the radiation thermometer reached 50°C. The test was conducted indoors at an air temperature of 20°C. The shorter the time to reach 50°C, the better the thermal conductivity of the insulator. Samples that took less than 20 seconds were rated A, samples that took 20 to 30 seconds were rated B, and samples that took 30 seconds or more were rated C. The results are shown in Table 1.

[0042] (evaluation) The adhesion of sample No. 1-20 was evaluated as S, A, or B, while sample No. 21-25 was evaluated as C. Sample No. 1-20 has an insulator made of ceramic particles and amorphous oxides, does not contain resin, has an average thickness of 1 μm to 50 μm, has an average particle size of 0.4 μm to 10 μm, and on the cut surface of the insulator, the area of ​​the ceramic particles relative to the area of ​​the insulator was 50% to 70%. It is therefore presumed that sample No. 1-20 has improved adhesion of the insulator to the conductor compared to sample No. 21-25.

[0043] Concerning adhesion, sample No. 7-20 was rated S or A, while sample No. 1-6 was rated B. Sample No. 7-20 had a value of X / N (maximum thickness X of the insulator divided by minimum thickness N) of 2.4 or less, so it is presumed that the adhesion of the insulator to the conductor was improved compared to sample No. 1-6.

[0044] Concerning adhesion, sample No. 15-20 was rated an S, while sample No. 7-14 was rated an A. Sample No. 15-20 contained amorphous oxides in the insulator mainly composed of Te or Bi, so it is presumed that the adhesion of the insulator to the conductor was further improved compared to sample No. 7-14.

[0045] The thermal conductivity of sample No. 1-20 was rated A or B, which indicates that the thermal conductivity of the insulator was also secured. In terms of thermal conductivity, sample No. 11-20 was rated A, while sample No. 1-10 was rated B. Since the ceramic particles contained in the insulator of sample No. 11-20 were made of aluminum nitride, silicon carbide, or silicon nitride, it is presumed that the thermal conductivity of the insulator is further improved compared to sample No. 1-10.

[0046] The present invention has been described above based on an embodiment, but the present invention is in no way limited to the above embodiment, and it can be easily inferred that various improvements and modifications are possible within the scope of the present invention without departing from the spirit of the present invention.

[0047] In the embodiment, the coil 10 is described in which the conductor 12 made of a rectangular wire is edgewise bent, but this is not necessarily limited to this. It is of course possible to make the coil 10 by bending the conductor 12 flatwise instead of edgewise. The conductor 12 is not limited to a rectangular wire, and it is of course possible to adopt other conductors. Examples of other conductors include a rectangular wire with a square cross section and a round wire with a circular cross section.

[0048] In the embodiment, the coil 10 is described as being a square tube with a rectangular outer shape as viewed in the axial direction, but this is not necessarily limited to this. It is of course possible for the coil 10 to have a square tube shape with a square or sector outer shape as viewed in the axial direction. It is of course possible for the coil 10 to have a cylindrical shape with a circular outer shape (including an elliptical or oval shape) as viewed in the axial direction.

[0049] In the embodiment, the coil 10 in which one conductor 12 is wound in a spiral shape around the axis C has been described, but the present invention is not necessarily limited to this. It is of course possible to use a coil 10 in which multiple conductors are wound in a spiral shape around the axis C.

[0050] In the embodiment, the coil 10 in which the conductor 12 is wound in a spiral shape along the axis C has been described, but this is not necessarily limited to this. It is of course possible to make the coil 10 in which the conductor 12 is wound in a spiral shape around the axis C so that the distance between the axis C and the conductor 12 gradually increases.

[0051] In the embodiment, the coil 10 in which the conductor 12 is wound in one layer in the radial direction has been described, but this is not necessarily limited to this. It is of course possible to form the coil 10 in which the conductor 12 is wound in multiple layers in the radial direction. [Explanation of symbols]

[0052] 10 Coil 11 Wire rod 12 Conductors 13 Insulators 14 Ceramic particles 15 Amorphous oxides C-axis P plane

Claims

1. A coil wound with a wire having a conductor and an insulator covering the conductor, the insulator is made of ceramic particles and an amorphous oxide; The average thickness of the insulator is 1 μm or more and 50 μm or less, The average particle size of the ceramic particles is 0.4 μm or more and 10 μm or less, In a cut surface of the insulator, an area of ​​the ceramic particles is 50% or more and 70% or less of an area of ​​the insulator, the material of the ceramic particles is at least one selected from aluminum nitride, silicon carbide, and silicon nitride; A coil, wherein the porosity of the insulation is 7% or less.

2. 2. A coil according to claim 1, wherein the value obtained by dividing the average maximum value of the thickness of the insulator appearing on a cross section cut along a plane perpendicular to the axis of the coil by the average minimum value is 2.4 or less.

3. 3. The coil according to claim 1, wherein the main component of the amorphous oxide is Bi or Te.

4. The coil according to claim 1 , wherein the material of the conductor is Cu or Al.

Citation Information

Patent Citations

  • Heat resistance insulating coil

    JP1981167305A

  • Manufacture of insulated wire and heat resistant insulated coil using the wire

    JP1987206706A

  • Manufacture of insulated coil

    JP1992085805A

  • Insulated coil

    JP1992303901A

  • Insulating film coating and insulated wire

    JP2011132393A